THE INFLUENCE OF PECULIARITIES OF CHILD-PARENTAL RELATIONSHIP ON THE FORMATION OF THE PERSONALITY OF A TEENAGER - Kharchenko I. A. (Social-Psychological Issues of a Contemporary Family: Value of Motherhood and Childhood, 2021)
This work examines the problem of creating harmonious relationships, a healthy psychological and comfortable climate in the family. The aim of the research is to study the problems arising in the relationship between parents and children on the way of personality formation in adolescence. Child-parental relations in the family occupy one of the most important places in the development of the child. Under the guidance of the father and mother, the child acquires his own first life experience, simple knowledge about the reality around him, skills and abilities of life in society. Forming the personality of a teenager is the most important task of parents. Adolescence is the time when there is an understanding of oneself in society, knowledge of the generally accepted framework of behavior and communication. The teenager is especially interested in social problems, values, life position is being laid. The personality of the child is formed under the influence of the type of parent
Keywords: развитие; родители; личность; personality; дети; самоанализ; development; ответственность; children; parents; responsibility; adolescence; подростковый период; отношения в семье; family relationships; introspection